Development of a math learning system for high school students using the Java desktop platform. (3rd July 2019) - Wibowo, Santoso; Moore, Paul; Li, Michael
This paper presents the development of a math learning system for high school math students. The development process involved the creation of the front-end graphical user interface and the back-end database, with both being implemented to near-commercial standard. The front-end consists of two main screens; a separate one each for the teacher and the student. The teacher's screen displays and allows the editing of all data in the database through the use of tables. The student is presented with all the math questions from the database on their screen in a structured form for the practice of math problems of various difficulty levels. Three types of final tests were performed to examine the effectiveness of math learning system. The results showed that the system is consistent and usable for learning math at high school.